2018
DOI: 10.1016/j.atmosres.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Thunderstorm characteristics favouring downward and upward lightning to wind turbines

Abstract: Meteorological conditions and thunderstorm characteristics related to lightning threats to wind turbines are discussed in this paper. Due to the rotating blades, wind turbines may be regarded peculiar tall objects, more susceptible to lightning strikes than other tall man-made structures. In the present study, Lightning Mapping Array and weather radar observations allowed to draw a clear picture of the thunderstorm characteristics leading to lightning strokes to wind turbines, in a coastal area of the Mediterr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 91 publications
1
15
0
Order By: Relevance
“…Contrary to high‐speed video, which may suffer from cloud screening effects, the LMA depicts lightning channels within the cloud with sufficient time resolution and spatial precision to locate their origin and propagation path. Relying on LMA data, Edens et al () and Hill et al (), have analyzed upward propagating leaders (UPL) on rocket‐and‐wire triggered lightning; Wang et al () and Schultz et al () have examined winter UL in Japan and the United States, respectively; and Montanyà et al () and Pineda, Montanyà et al () have studied ULs emerging from wind turbines. These works have revealed that UL are linked to particular meteorological regimes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to high‐speed video, which may suffer from cloud screening effects, the LMA depicts lightning channels within the cloud with sufficient time resolution and spatial precision to locate their origin and propagation path. Relying on LMA data, Edens et al () and Hill et al (), have analyzed upward propagating leaders (UPL) on rocket‐and‐wire triggered lightning; Wang et al () and Schultz et al () have examined winter UL in Japan and the United States, respectively; and Montanyà et al () and Pineda, Montanyà et al () have studied ULs emerging from wind turbines. These works have revealed that UL are linked to particular meteorological regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al () pointed out that lower ambient temperature may also have an effect on the initiation of upward leaders: keeping in mind the dependence of the electrification processes on temperature (e.g., Saunders et al, ; Takahashi, ), cloud charges are at lower altitudes in winter, favoring interaction with ground structures such as towers and wind turbines, as reported in the literature (Wang & Takagi, ; Schultz et al, ; Pineda, Bech et al, ). Lately, studies such as Warner et al (), Jiang et al (), Wang et al (), and Pineda et al () have incorporated weather radar data into the analysis, providing a comprehensive survey on the thunderstorm characteristics related to UL.…”
Section: Introductionmentioning
confidence: 99%
“…Keeping in mind the dependence of the electrification processes on temperature (e.g. Takahashi, 1978;Saunders et al, 2006), cloud charges are at lower altitudes in winter, favoring interaction with ground structures such as wind turbines, as reported in literature (Wang and Takagi, 2012;Montanyà et al, 2014;Schultz et al 2018;Pineda et al 2018a;Soula et al, 2019). Consequently, the concept of winter lightning has been recently introduced and conceptualized in the 2018 revision of the "Lightning Protection of Wind Turbines" standard IEC 61400-24 (Méndez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…3 Most of winter lightning to tall structures belong to the upward lightning type. Studies like Warner et al (2014), Jiang et al (2014), Schultz et al (2018), Bech et al (2013) and Pineda et al (2018a) have shown that enhanced electric fields at the top of tall structures, combined with a lower altitude of the charge centers (e.g. Montanyà et al, 2016) were enough to allow the initiation of upward lightning.…”
Section: Introductionmentioning
confidence: 99%
“…Damages to WTGs by lightning is currently one of the main sources of WTG insurance claims and downtime [48]. The wind turbine structures can easily attract the wrath of storms and the rotation of the blades may also trigger lightning and result in a considerable increase in the number of strikes to a WTG [50][51][52]. Lightning damage is the single largest cause of unplanned downtime in WTGs, and that downtime is responsible for the loss of countless megawatts of power generation [48].…”
Section: Incidence Of Lightning Strikes On Wind Turbinesmentioning
confidence: 99%